(3GdMeGjI GdLfGFjI ddMb aj MQeI GdeScf aj GdbGfhf GdhVYj hGdabg GdESdGej (B/ s - (3eUWai ESeGYjd MejO YHO GdbGOQ s; (3MSfjf EHQGgje UGdM YHjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI(B, s, 2016)
(3Ef GdMb ai MQeI GdeScf jYO Gge YfGUQ GdMb ai MQeI GdMjGI GdNGUI hdjS dg eaghe eMOO ai GdJTQjYGJ GdhVYjI hdjS dg eaghe eSJbQ Ydjg ai Gdabg hGdbVGA hbO JHjf Gf GdTQjYI GdGSdGejI bO hUdJ Gdi GbUi OQLGJ GdMeGjI dgPG GdMb HNdGa GdJTQjYGJ GdhVYjI GdJi GWgQJ GdOQGSI Gf gfGc bUhQG HgG ShGA ef fGMjI GdMeGjI GdehVhYjI Gh GdGLQGFjI hef gPG GdbUhQ YOe JLQje GdeSGQbI GdHUQjI HGdYjf GdeLQOI hYOe JLQje HbGA GdehXa GdYGe ai efRd GdZjQ Ohf QVGg hYOe JLQje ONhd efRd GdZjQ GdG ai MGdI bUO GQJcGH LQjeI GNQi Gh SdH MjGRJg HGdbhI hYOe MXQ GLQGA GdJaJjT djdG hYOe JMOjO eaghe Gddjd ai GdbGfhf GdLfGFis
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2016s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B461-493s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdMeGjI GdLfGFjIs; (3GdbGfhf GdhVYj s; (3MQeI GdeScf s; (3MQeI GdMjGI GdNGUI s; (3MQeI GdeQGSdGJs; (3GdJLSS GdSeYj hGdHUQj s; (3JaJjT GdefGRd s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs